(untitled) (Journal of Pakistan Orthopaedic Association, 2024)
Objectives: The clinical study was carried out to establish the frequency of deranged pulmonary function tests (PFTs) in patients suffering from adolescent idiopathic scoliosis (AIS). Methodology: All the patients consulting to the OPD of the department with scoliosis were gone through the diagnosis of AIS as per operational definition and patients complying the criteria of inclusion were included in the study. A comprehensive clinical history was obtained succeeded by detailed bodily and systemic examination. Cobb angle was measured using standard technique and type of scoliosis was classed according to standard Lenke Classification system. All patients were then sent to pulmonology department for assessment of derangement in pulmonary function tests (PFTs) and derangement in PFTs was defined as per operational definitions. Results: Out of 88 patients, 76.1% were males and 23.9% were females. Mean age was 13.39 ± 1.86 years and mean Cobb angle was 45.03 ± 16.2 ºs. Maximum patients were of 10-12 years age i.e. 35.2%. Most patients (34.1%) were observed with 41-55 º Cobb angles. 30.7% patients were with Type 2 curve. 38.6% patients were observed with moderately severe deformity, followed by 28.4% patients with moderate severity. The curve was structural in 86.4% patients while non-structural in 13.6% patients. Deranged PFTs were observed in total 64.8% patients. Conclusion: Pulmonary Function Tests (PFTs) like FVC and FEV1 are highly associated with AIS and preoperative PFTs are very helpful in planning and management of the surgery of patients with scoliosis.